Pengaruh Kepemimpinan Situasional, Sistem Pengukuran Kinerja, dan Penerapan Teknik Total Quality Management terhadap Kinerja Manajerial (Studi Empiris Pada PT. Telkom Kandatel Jember) - Dwi Hidayati (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
This study aims to test the Influence of Situational Leadership, Performance Measurement System, and Application Techniques of Total Quality Management"and perform empirical studies on PT. Telkom Kandatel Jember. Population andsamples in this study were middle managers, assistant managers and officers in PT.Telkom Kandatel Jember some 113 people. The analytical method used is multiple linear regression analysis. After analyzing the data, some conclusions can be drawn: a). Results of the study received that leadership is situational influence on managerial performance of PT. Telkom, Tbk Kandatel Jember. Influential situational leadership on managerial performance of PT. Telkom, Tbk Kandatel Jember indicate that situational leadership in the form adopted by the leaders of PT. Telkom, Tbk Kandatel Jember has been able to improve the performance of managerial PT. Telkom, Tbk Kandatel Jember. b). Systems affect the performance of managerial PT. Telkom, Tbk Kandatel Jember. Influential performance measurement systems on managerial performance of PT. Telkom, Tbk Kandatel Jember indicate that the majority of managers has made efforts to improve quality, service process integration, to make efforts aimed at reducing the cost of service due to the interference re convenience, in order to satisfy customers, c). The application of TQM techniques affect the managerial performance of PT. Telkom, Tbk Kandatel Jember. Keywords: Situasional Leadership, Systems Affect the Performance, Total Quality Management, Performance